Features of studying the efficiency of fire protection of a wooden wall with external exposure to the flame of combustible substances - Tsapko, Yu.; Bondarenko, O.; Pinchevska, О.; Buys’kykh, N.; Lakida, Yu. (My University, 2019)
The article analyzes the physical ways to provide the necessary limit of fire resistance of wooden structures, which have significant disadvantages, namely, leading to significant material costs and increase the volume of structures. Modern methods of fire protection of building structures are based on the use of blocking coatings, which are complex systems of organic and inorganic components. Studies of the combustibility of wood have shown that a raw specimen of timber construction is capable of engaging and spreading flames on the surface. Instead, the structure treated with the organo-mineral protective coating did not burn after combustion of the model hearth, respectively, and did not break down. The swelling of the protective coating was recorded, and the temperature on the reverse floor was less than 140ºC. As a result, it was ascertained that the effectiveness of the shredded image of the tree’s construction was 4.4 times higher for the protected organic and mineral coatings 3.3 times higher - for the clear protection of non-organic ones. It’s necessary to assimilate a coke ball on the surface of the construction, which will add to the temperature and the temperature glyphine, with which the hour of reaching the boundary temperature will be improved.
Keywords: fire protection; wooden wall; flame; combustible substances